CURRENT TRENDS IN THE DEVELOPMENT OF TECHNOLOGY FOR THE APPLICATION OF BULK ORGANO-MINERAL FERTILIZERS - RUTKEVYCH, VOLODYMYR; KAJURO, MAXIM (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The development of equipment for applying organo-mineral fertilizers is an important step in ensuring sustainable agricultural development, increasing the efficiency of fertilizer use and reducing the negative impact on the environment. Modern spreaders used for mineral fertilizers cannot work effectively with organo-mineral mixtures due to their heterogeneity, variable density and tendency to caking.  Existing problems include uneven distribution of fertilizers, the formation of lumps due to high humidity of organic components, as well as insufficient dosing accuracy. This emphasizes the need to create specialized spreaders that can accurately dose and evenly distribute organo mineral mixtures.  Studies indicate the need to develop specialized spreaders for applying organo-mineral fertilizers that take into account their heterogeneity. One of the promising technologies is the use of precision farming systems that use moisture sensors and geoinformation technologies to accurately control fertilizer application. The current state and prospects for the development of technical means for applying loose organo mineral fertilizers (OMD) are considered. Existing types of equipment for applying mineral and organic fertilizers are analyzed, their limitations in working with heterogeneous mixtures of organo-mineral type are noted. The urgent need for the development of specialized OMD spreaders capable of ensuring uniform distribution and accuracy of dosing, taking into account the physical and mechanical properties of fertilizers, is emphasized. Key areas of further engineering and technological research are proposed, in particular the creation of intelligent control systems, the use of automated platforms and the introduction of energy-saving technologies.  The results obtained can be used to develop effective new generation equipment to increase the efficiency of fertilization and reduce the environmental load in agricultural production.
Keywords: organo-mineral fertilizers; mineral raw materials; soil fertility; equipment; working bodies; hydraulic drive; productivity